Correlation between resilience and cognitive functioning in veterans with traumatic brain injury - D.O. Assonov (Medičnì Perspektivi, 2023)
Resilience in veterans with brain trauma in remote period has received considerable attention over the past years. Cognitive functioning is described among factors that may influence resilience and included in the modern theoretical models of this positive psychology phenomenon. However, the characteristics of relationship between resilience and cognitive functioning in veterans with traumatic brain injury (TBI) in remote period was not studied empirically. Therefore, the purpose of this study was to gain better understanding of the possible association between resilience and cognitive functioning in Ukrainian war veterans with traumatic brain injury in remote period. This study included 146 veterans who were admitted to two clinical hospitals for war veterans. The Connor-Davidson Resilience Scale and Montreal Cognitive Assessment Scale were used. The present study shows that lower cognitive functioning in total and in several domains is associated with less effective resilience regardless of TBI clinical type (whether it is concussion or mild cerebral contusion). Moreover, such correlation was still present after excluding the effect of age, education and TBI characteristics like number of traumas and time since last TBI.  Overall, we found empirical evidence that good cognitive functioning (especially executive functions, memory, attention, abstract thinking, and orientation) is essential for effective resilience in veterans with mild TBI even years after trauma and has more effect on ability to adapt than age, education, and trauma characteristics. Educating veterans to use their cognitive potential and to compensate the restrictions after mild TBI possibly may lead to better overcoming adversities and counteracting the risks of desadaptation and traumatic events. Therefore, psychological interventions for improving the ability to readapt and recover possibly should consider this relationship and include the component of educating veterans to use their cognitive reserve and compensate limitations to better adapt and thrive. Studies related to such interventions appear to be promising.